1968
DOI: 10.1104/pp.43.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for an Elongation-Decarboxylation Mechanism in the Biosynthesis of Paraffins in Leaves

Abstract: Abstract. In isolated tobacco leaves L-valine-U-14C gave rise to labeled even-numbered isobranched fatbty acids containing 16 to 26 carbon atoms and iso C29, iso C31, and iso C3, paraffins. L-Isoleucine-U-14C on the other hand produced labeled odd-numbered anteiso C17 to C97 fatty acids and anteiso C30 and C32 paraffins. Trichloroace'tic acid inhibited the incorporation of isobutyrate into C90 and higher fatty acids and paraffins without affecting the synthesis of the Cl. and C,, fatty acids. Thus the very lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 16 publications
1
35
0
2
Order By: Relevance
“…Although considerably less is known about elongation beyond lengths of 16 carbons, as must occur in wax biosynthesis, presumably an analogous set of enzyme reactions is required at each elongation step. Epicuticular wax biosynthesis which is carried out by epidermal cells (2, 14) consists not only of the elongation steps but also of the associated pathways giving rise to the various lipid classes. Thereafter the wax is deposited on the cuticle surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Although considerably less is known about elongation beyond lengths of 16 carbons, as must occur in wax biosynthesis, presumably an analogous set of enzyme reactions is required at each elongation step. Epicuticular wax biosynthesis which is carried out by epidermal cells (2, 14) consists not only of the elongation steps but also of the associated pathways giving rise to the various lipid classes. Thereafter the wax is deposited on the cuticle surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies indicate a-KAE for short branchedchain production in tobacco and Petunia acyl sugars (Kroumova and Wagner 2003). FAS elongation appears to be employed for branched-chain wax components in tobacco species, however (Kaneda, 1967;Kolattukudy, 1968;Kroumova and Wagner, 1999).…”
Section: Involvement Of Fas In Bcfa Elongation and Its Association Wimentioning
confidence: 99%
“…In primary metabolism, these steps are associated with Leu synthesis, but here choice of substrate is evidently wider (Kroumova and Wagner, 2003;Field et al, 2006). Interestingly, iso-and anteiso-branched chains are also significant components of wax alkanes, epicuticular esterified alcohols, and fatty acids in tobacco species, but according to isotope-labeling studies, the latter are generated by FAS-mediated elongation of branched-chain precursors rather than a-KAE (Kaneda, 1967;Kolattukudy, 1968;Kroumova and Wagner, 1999).…”
mentioning
confidence: 99%
“…The esters were identified by co-GLC with barley esters and a C50 standard (synthesized by P. AVATO). The conclusions drawn were confirmed by subjecting the total esters to MS. Transmethylation of the maize esters was not complete in 24 …”
Section: Methodsmentioning
confidence: 99%
“…The effect of CI3AcONa on wax synthesis has been examined in a number of plant systems (8,21,23,24,26,30,32,38). Initial studies with intact leaves of B. oleracea revealed that Cl3AcONa concentrations up to 5 vmol/leaf inhibited incorporation of acetate into hydrocarbons, secondary alcohols and ketones much more severely than that into primary alcohols, free fatty acids and esters (2 I).…”
Section: Inhibitors and Fatty Acyl Elongationmentioning
confidence: 99%